Nutritional status of Vietnamese infants assessed by Fenton growth chart and related factors: A cross‐sectional study - Lieu Thu Thi Nguyen; Cuong Danh Tran; Ha Thu Thi Nguyen; Hai Thanh Phan; Linh Thuy Nguyen; Huong Lan Thi Nguyen; Anh Hoai Thi Ta; Chau Quynh Thi Pho; Khanh Nam Do; Anh Kim Dang; Huong Thi Le (Wiley, 2023)
ABSTRACT Importance Nutritional status of infants, measured by birth weight and length, is an essential factor in neonatal development. Malnutrition in newborns may lead to a higher risk of mortality, neurological and cognitive impairment, and poor language development. Objective This study aims to assess the nutritional status of infants and related factors regarding maternal anthropometric characteristics and medical history. Methods A cross‐sectional study was conducted at the National Hospital of Obstetrics and Gynecology, Vietnam from May 2021 to May 2022 on 340 infants and mothers. Low birth weight was defined following the Intergrowth‐21 standards. Stunting was evaluated using the Fenton growth chart when the length was below the 10% percentile line of the gestational week. Multivariate regression models were applied to identify factors associated with the nutritional status of infants. Results We found that 12.4% and 14.1% of infants in our study fell into stunted and underweight categories, respectively. Infants of mothers over 35 years old, having a height lower than 150 cm or experiencing anemia during pregnancy were more likely to be stunted or have low birth weight. Serum albumin deficiency during pregnancy was strongly associated with the infant being underweight (odds ratio [OR]  =  2.8, 95% confidence interval [95%CI] 1.1-7.3). Newborns were more likely to be stunted if their mothers had a history of preterm birth (OR = 3.3, 95%CI 1.1-10.2). Interpretation Maternal nutritional status is closely related to infant malnutrition, particularly in preterm infants. Improving the understanding of mothers regarding prenatal care, reproductive healthcare, adequate nutritional diet, and multi‐micronutrient supplements during pregnancy is therefore important.